2002
DOI: 10.1097/00061198-200206000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar Chlorpromazine Injections for the Management of Blind and Seeing Painful Eyes

Abstract: Retrobulbar chlorpromazine appears to be safe and effective for the management of pain in blind eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…[9][10][11]25,26] Both of them caused less pain compared with alcohol, and they acted faster in alleviating the pain. [9,11] Very few studies on either alcohol or other neurolytics use are available. The characteristics of neurolytic agents that make them better than other methods are that they are more comfortable, their effect length is shorter, and they are cheaper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]25,26] Both of them caused less pain compared with alcohol, and they acted faster in alleviating the pain. [9,11] Very few studies on either alcohol or other neurolytics use are available. The characteristics of neurolytic agents that make them better than other methods are that they are more comfortable, their effect length is shorter, and they are cheaper.…”
Section: Discussionmentioning
confidence: 99%
“…[5] It has been reported that some agents such as ethyl alcohol, phenol, or chlorpromazine are effective from 2 weeks to 2 years in 30%-87% of the cases. [5][6][7][8][9][10][11] This study aimed to evaluate the severity and complications of the retrobulbar ethyl alcohol injection in patients Original Article having NVG-dependent therapy-resistant severe pain using the verbal analog scale (VAS).…”
Section: Introductionmentioning
confidence: 99%
“…If conservative measures do not result in improved comfort for the patient, then pain can be relieved with retrobulbar injection of chlorpromazine55 or absolute alcohol. If this is not effective, or there is a cosmetic concern, then evisceration or enucleation can be considered with an ocular prosthesis as appropriate.…”
Section: Blind Painful Eye(s) With Glaucomamentioning
confidence: 99%
“…Pain can, at times, be controlled with a retrobulbar injection of alcohol or chlorpromazine 57–59. Corneal-related discomfort can, in select cases, be managed with a conjunctival flap 6064…”
Section: Indicationsmentioning
confidence: 99%